Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Kulit Bawang Merah dan Air Cucian Beras (Leri) Pada Ibu Rumah Tangga Di Desa Mekar Sari, Kecamatan Tanjung Raya Kabupaten Mesuji - Leoninda, Alfiyani; Nopriansyah, Untung; Rahmawati, Iis; Zulkifli; Desilia; Deka Pusanti, Seli (LPPM STKIP PGRI Pacitan, 2024)
This community service project in the form of training was carried out based on the collaboration of KKN students from UIN Raden Intan Lampung and the community of Mekar Sari Village, in Tanjung Raya District, Mesuji Regency, Lampung Province, in order to provide training on community-friendly products for making liquid organic fertiliser from household waste to fertilise plants. The method used is counselling and providing training to the community, especially housewives. The purpose of this service is to educate and manage household waste as plant fertilizer. As a result, people are very aware that household vegetable waste, which is reprocessed into liquid organic fertiliser, has benefits for fertilising plants.